From self-sufficiency to dependence on imported food-grain in Leh District (Ladakh, Indian Trans-Himalaya) - Pelliciardi, Vladimiro (European Journal of Sustainable Development, 2013)
For many centuries the population of Ladakh (Indian Trans-Himalaya) has led a self-reliant existence mainly based upon subsistence agriculture (self-sufficient in food-grainproduction), pastoralism and caravan trade. Since several decades, Leh District, a part ofLadakh, whose population is doubled from about 70000 in 1981 to 145000 in 2011, is nomore self-sufficient in food-grain production. To overcome the demand-supply imbalancea large quantity of rice and flour wheat is imported every year by traders, cooperatives andcentral government. However to be self-sufficient is an important issue for this landlocked territory which has not trade restrictions but severe constraint in transportation.Importing goods to Ladakh necessitates the shipping of goods by truck across theHimalayas, with passes as high as 5300 m, covering the distance of Manali to Leh (480 km)or Srinagar to Leh (420 km) will takes about three days. By plain is only one hour of flybut cargo airfares are very costly.The stocking of the essential items, like food grains, inLadakh, by the Jammu and Kashmir government, is an annual practice ahead of harshwinters which cuts off by road, for seven-height months, the twin districts of Leh andKargil from the rest of the country. Filling the gap between the required quantity to feedthe growing population and the quantity locally produced can be a difficult task in thishigh altitude cold desert region. Quantifying those “needs” helps developing policy andprogrammatic decision in regard to the local food security problem. In this study, the LehDistrict dependence on imported food-grain is investigated and results are presented asImport Dependency Ratio (IDR) in 2012 and the expected value in 2025.